1987
DOI: 10.1002/food.19870310572
|View full text |Cite
|
Sign up to set email alerts
|

Problems of space gastroenterology and microenvironment

Abstract: Numerous studies have revealed changes in gastrointestinal secretion, motility, evacuation, and absorption in humans and animals after actual space missions and under hypokinesia of various duration as well. It is found that short-term space missions produce transient changes in the activity of digestive enzymes, instability of bifido- and lactoflora peculiar to stress reaction, and an enhanced evacuation of the stomach. Extended space missions result in more pronounced but transient changes which characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Microgravity or simulated weightlessness has been shown to induce dysbiosis in intestinal microbiota ( Smirnov and Lizko, 1987 ; Li et al, 2015 ; Ritchie et al, 2015 ). The present study indicated that hindlimb unloading increased proportion of Bacteroidetes and decreased Firmicutes -to- Bacteroidetes (F:B) ratio compared with the CON, which are in accordance with the change of intestinal microbiota during 13-days spaceflight ( Ritchie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microgravity or simulated weightlessness has been shown to induce dysbiosis in intestinal microbiota ( Smirnov and Lizko, 1987 ; Li et al, 2015 ; Ritchie et al, 2015 ). The present study indicated that hindlimb unloading increased proportion of Bacteroidetes and decreased Firmicutes -to- Bacteroidetes (F:B) ratio compared with the CON, which are in accordance with the change of intestinal microbiota during 13-days spaceflight ( Ritchie et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a renewed interest concerning that intestinal microbiota may be influenced by environmental and genetic factors, diet and probiotics, which also affect the host health and behavior in turn ( Faust and Raes, 2016 ). Compositional changes in intestinal mucosal microbiota have been reported during short and long-term spaceflight, which indicated that microgravity could perturb the structure and composition of intestinal bacterial communities ( Nefedov et al, 1971 ; Smirnov and Lizko, 1987 ; Ritchie et al, 2015 ). However, studies on how commensal bacteria respond to weightlessness at species level and the influence of weightlessness on their functionality and metabolic activities are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our cohousing experiments demonstrated for the first time a close relationship between gut dysbiosis and peripheral insulin resistance/glucose intolerance in HU mice. As gut dysbiosis has been found in astronauts and rodents during short-and long-term space missions (20)(21)(22)(23)(24)(25), it is very likely that altered intestinal microbiota also contributes to spaceflight-induced glucose metabolic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…ABBREVIATIONS: AUC, area under curve; c-Ctrl, cohoused Ctrl; Ctrl, control; c-HU, cohoused HU; G6pc, glucose-6-phosphatase; Gck, glucokinase; GTT, glucose tolerance test; HOMA-IR, homeostasis model assessment of insulin resistance; HU, hind limb unloading; ITT, insulin tolerance test; LBP, LPS-binding protein; OTU, operational taxonomic unit; PCoA, principal coordinate analysis Dysbiosis has also been found during short-and long-term space missions, with a reduction in the beneficial group of microorganisms, such as Bifidobacterium and Lactobacillus, and an accumulation in opportunistic pathogens, such as Escherichia coli, Pseudomonas aeruginosa, Fusobacterium nucleatum, and Clostridium spp. (20)(21)(22)(23)(24)(25)(26). This indicates that conditions in space, whether they be microgravity, radiation, stress, or diet (27), could alter the composition and structure of intestinal microbial communities.…”
mentioning
confidence: 99%
“…Furthermore, extended isolation of a person, as in the case of a long space flight or special trainings, modifies the intestinal microbiota (32). It is also extensively discussed that stress influences the gut microbiota.…”
Section: Environment Stress Antibiotics and Other Factors Alteringmentioning
confidence: 99%